1986
DOI: 10.1128/mcb.6.2.511
|View full text |Cite
|
Sign up to set email alerts
|

Structure, expression, and chromosomal location of the human c-fgr gene.

Abstract: The nucleotide sequence of seven exons of the human c-fgr gene, a cellular homolog of the oncogene of Gardner-Rasheed feline sarcoma virus, was determined. Twenty-six independent genomic clones were obtained from a human gene library with a DNA clone of Y73 avian sarcoma virus oncogene, v-yes, as a probe under relaxed hybridization conditions. Restriction mapping and partial sequence analyses revealed that two of these clones were derived from the c-fgr gene, distinct from the c-yes gene. Interestingly, the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Sequences from regions of overlap with previously published genomic sequences (Parker et al, 1985;Nishizawa et al, 1986) exhibited 100% homology (data not shown). The sequence of the 5' end of the c-fgr mRNA, derived from clones pFd97 and pFa4, is shown in Figure 3 contain downstream termination codons, and the reading frame indicated is in phase with previously predicted aminoacid sequence .…”
Section: Isolation Of C-fgr Cdna Clonesmentioning
confidence: 91%
See 2 more Smart Citations
“…Sequences from regions of overlap with previously published genomic sequences (Parker et al, 1985;Nishizawa et al, 1986) exhibited 100% homology (data not shown). The sequence of the 5' end of the c-fgr mRNA, derived from clones pFd97 and pFa4, is shown in Figure 3 contain downstream termination codons, and the reading frame indicated is in phase with previously predicted aminoacid sequence .…”
Section: Isolation Of C-fgr Cdna Clonesmentioning
confidence: 91%
“…Restriction maps of the inserts of the three longest clones (pFal, pFcl l & pFd97), each from the RPMI 4265 cDNA library, are shown in Figure 2. Together, the three clones span 2,347bp and the restriction maps of their central regions are colinear with previously published partial restriction maps of the c-fgr transcript, predicted from the sequences of genomic clones (Parker et al, 1985;Nishizawa et al, 1986).…”
Section: Isolation Of C-fgr Cdna Clonesmentioning
confidence: 98%
See 1 more Smart Citation
“…This is primarily because v-fgr is linked to the actin sequence at its amino terminus in the feline sarcoma virus genome (25,26,28), whereas c-fgr is not fused with actin sequences and may share homology with the amino-terminal region of c-yes. A published sequence of the human c-fgr protein in this region (29) indicates an homology of 20 of 24 amino acids in the carboxyl end of the v-yes polypeptide expressed as cI-yes-lacIZ.…”
Section: Discussionmentioning
confidence: 99%
“…Other genes in this family (the src family) are c-yes, c-fgr, fyn, hck, tkl, and lyn (17,25,26,29,34,36,37,40,42,43; for a review, see J. A. Cooper, in B. Kemp and P. F. Alewood, ed., Peptides and Protein Phosphorylation, in press).…”
mentioning
confidence: 99%